Pro core data for iOS data access and persistence engine for iPhone, iPad, and iPod touch - Privat, Michael (Apress, 2011)
Fully updated for Xcode 4.2, Pro Core Data for iOS explains how to use the Core Data framework for iOS SDK 5 using Xcode 4.2. The book explains both how and why to use Core Data, from simple to advanced techniques. Covering common and advanced persistence patterns, this book prepares any iOS developer to store and retrieve data accurately and efficiently. This book starts by giving you a solid grounding in Core Data, providing a foundation for the rest of the book. With this knowledge, you'll have all you need to master Core Data and power your data-driven applications. You'll see how to work with SQLite and how to create an efficient data model to represent your data. Once you've established your data model, you'll learn how to work with data objects and refine result sets to get the most out of the stored data. The advanced portions of the book begin by showing you how to tune your apps' performance and memory usage, to give you a truly professional edge. You'll see how to version and migrate your data as well, to ensure your data stays organized and efficient.Â Finally, the book covers managing table views with NSFetchedResultsController.